Selected elements of the lifestyle of Silesian seniors, taking into account their participation in the activities of the Third Age Universities - Dąbek, Józefa; Szynal, Magdalena; Łebek, Ewelina; Sierka, Oskar (Frontiers in Public Health, 2024)
UTA can provide elderly people with the satisfaction of needs and creates the opportunity to pursue youthful interests and passions. The aim of the study was to assess selected elements of the lifestyle of Silesian seniors, taking into account their participation in the activities of Universities of the Third Age. The study involved 631 (100%) senior residents of the Silesian agglomeration. The majority of the study group were women (475; 75.28%), and the average age of the participants was 70.28±6.09 years. To conduct the study, an original survey questionnaire was used, complemented by PPS-10, PAQE and Yesavage Geriatric Depression Rating Scale. Among the surveyed Silesian seniors who did not attend classes at the University of the Third Age, a statistically significantly higher score on the Yesavage’s Geriatric Depression Rating Scale was found compared to those confirming their participation in the mentioned activity (p=0.002). Almost 40% (107; 38.63%) of seniors who did not attend classes at the Universities of the Third Age showed a high level of stress, and every fourth (89; 25.14%) Silesian senior taking part in the above-mentioned activity had a low level of stress (p=0.04). The median of points obtained on the physical activity assessment scale (PAQE) by seniors attending classes at Universities of the Third Age was statistically higher than seniors who denied participation in the mentioned activity (p=0.017). Participation in the various activities at the Universities of the Third Age influenced positively well-being, reduced stress and raised physical activity of examined seniors. It is important to promote and start actions leading to seniors’ better and easier inclusion to the society life. Future research should concentrate on reasons why many seniors do not attend activities in their leisure time - especially on accessibility of various activities and financial reasons, which in the future will play crucial role in the aging societies.